Liderazgo femenino y su relación con el proceso de toma de decisiones en la gestión administrativa en el personal administrativo de la Corte de Justicia de Loreto año 2024 - Garcia Mafaldo, Karenn Siuth (2025)
Women still face significant barriers to achieving leadership roles, which limits equity and organizational development, it is highlighted that female leadership improves efficiency, cohesion and sustainability, and advocates for initiatives to break down obstacles such as the glass ceiling and gender stereotypes. For this reason, the present study aims to identify the relationship between female leadership and the decision-making process in administrative management in the administrative staff of the Loreto Court of Justice in 2024 from a quantitative, observational approach and a non-experimental design considering a population made up of the administrative staff of the Loreto Court of Justice, amounting to 127 people. The results revealed a high and significant positive correlation between both variables (rho = 0.745; p = 0.000), confirming that female leadership strengthens the quality of administrative decisions. At the specific level, a strong positive relationship was found with analytical (rho=0.715), strategic (rho=0.719), and participatory (rho=0.701) decision making, demonstrating that female leadership enhances not only evaluative effectiveness but also long-term vision and inclusion in administrative processes. Descriptively, it was identified that female leadership is widely valued in competencies such as communication, emotional management, and ethical responsibility, while decision-making processes are perceived as strategic, analytical, and participatory. In conclusion, female leadership plays a decisive role in improving administrative management, reinforcing both the technical and human dimensions of decision-making, which highlights the need to continue promoting and strengthening the development of female leaders in strategic institutional environments.